2021
DOI: 10.3390/cancers13092255
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3 Inhibits the Angiogenic Potential of Multiple Myeloma Cells

Abstract: During multiple myeloma (MM) progression the activation of the angiogenic process represents a key step for the formation of the vascular niche, where different stromal components and neoplastic cells collaborate and foster tumor growth. Among the different pro-angiogenic players, Fibroblast Growth Factor 2 (FGF2) plays a pivotal role in BM vascularization occurring during MM progression. Long Pentraxin 3 (PTX3), a natural FGF antagonist, is able to reduce the activation of stromal components promoted by FGF2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…21 A study conducted in MM patients indicated that PTX3 levels were higher in samples obtained from fibroblast, endothelial, and PC cultures compared to control groups. 12 In this context, the results we obtained are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…21 A study conducted in MM patients indicated that PTX3 levels were higher in samples obtained from fibroblast, endothelial, and PC cultures compared to control groups. 12 In this context, the results we obtained are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…11 Cell culture studies have demonstrated that elevated PTX3 application reduces angiogenesis and progression of MM cells by sequestering FGF2, which is an anti-tumor characteristic of PTX3. 12 Nevertheless, a study conducted in chronic lymphocytic leukemia (CLL) patients indicated that down-regulation of PTX3 enhances apoptosis in CLL cells, which is a pro-tumor characteristic of PTX3. 13 These studies reveal dual role of PTX3 in oncogenesis, exhibiting both pro-tumor and anti-tumor properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an increased FGF/PTX3 ratio occurs during MM evolution. In a recent study, PTX3 overexpression was found associated with significantly reduced tumor burden in MM models (Ronca et al 2021).…”
Section: Discussionmentioning
confidence: 94%
“…However, in contrast to the hepatic protein CRP, PTX3 is produced by different cell types including endothelial cells. PTX3 has dual roles in angiogenesis, since it has both anti- and pro-angiogenic properties ( 39 , 40 ). In this study, mean plasma PTX3 did not differ significantly between the ET and control cohorts.…”
Section: Discussionmentioning
confidence: 99%